2020
DOI: 10.21203/rs.3.rs-19834/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Bioproduction of succinic acid from xylose by engineered Yarrowia lipolytica without pH control

Abstract: Background Xylose is a most prevalent sugar available in hemicellulose fraction of lignocellulosic biomass (LCB) and of great interest for the green economy. Unfortunately, most of the cell factories cannot inherently metabolize xylose as sole carbon source. Yarrowia lipolytica is a non-conventional yeast to produce industrially important metabolites, and it is able to metabolize a large variety of substrates including both hydrophilic and hydrophobic carbon sources. However, Y. lipolytica lacks effective met… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3
1

Relationship

3
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 51 publications
0
7
0
Order By: Relevance
“…Although Y. lipolytica has endogenous genes for pentose catabolism (Ryu et al, 2016;Ryu and Trinh, 2018) this yeast cannot use xylose as a sole carbon source (Ledesma- Amaro et al, 2016;Niehus et al, 2018;Ong et al, 2019;Prabhu et al, 2020). Conversely, a synergistic effect of mixed-sugar utilization was reported in Y. lipolytica (Ryu et al, 2016;Ryu and Trinh, 2021), where xylose could be utilized in the presence of a glucose-xylose mixed sugar feedstock.…”
Section: Discussionmentioning
confidence: 99%
“…Although Y. lipolytica has endogenous genes for pentose catabolism (Ryu et al, 2016;Ryu and Trinh, 2018) this yeast cannot use xylose as a sole carbon source (Ledesma- Amaro et al, 2016;Niehus et al, 2018;Ong et al, 2019;Prabhu et al, 2020). Conversely, a synergistic effect of mixed-sugar utilization was reported in Y. lipolytica (Ryu et al, 2016;Ryu and Trinh, 2021), where xylose could be utilized in the presence of a glucose-xylose mixed sugar feedstock.…”
Section: Discussionmentioning
confidence: 99%
“…Y. lipolytica lacks an effective metabolic pathway for xylose uptake. Efforts have been made to engineer strains that can use xylose as a sole carbon source in the media (45). Due to the ability of engineered strains in a co-culture system to uptake and deal with the mixed feedstock in media and the weakness of Y. lipolytica to uptake xylose as a sole sugar source, we studied co-utilization of 20 g/L xylose with 20 g/L glucose.…”
Section: The Effect Of Xylose Co-utilization With Glucose On Amorphad...mentioning
confidence: 99%
“…It is noteworthy that L-MA production decreased slightly from day 5 to day 7, which may be due to the limitations of xylose in utilization under the late stationary growth phase, and the possibility to convert small amounts of L-MA to other metabolic intermediates under the TCA cycle. Prabhu et al [38] reported that after the maximum production of succinic acid from xylose by Yarrowia lipolytica, the succinic acid is reduced because it is converted to other by-products. On the other hand, the pH decreased slightly from 6.95 to 6.07 due to the formation of L-MA.…”
Section: Conversion Of Xylose Derived From Corn Hull To L-ma By a Tropicalis H1mentioning
confidence: 99%